That time I got reincarnated as a slime. 3 - Fuse (Manga author) (Kodansha Comics, 2017)
"Living alone and never having had a girlfriend, 37-year-old Satoru Mikami is dissatisfied with how his life has turned out. But after dying at the hands of a robber, he awakens to a fresh start in a new world...as a slime monster"--